A Wound-Healing Assay Based on Ultraviolet Light Ablation. (February 2017) - Wu, Shang-Ying; Sun, Yung-Shin; Cheng, Kuan-Chen; Lo, Kai-Yin
Collective cell migration plays important roles in many physiological processes such as embryonic development, tissue repair, and angiogenesis. A "wound" occurs when epithelial cells are lost and/or damaged due to some external factors, and collective cell migration takes place in the following wound-healing process. To study this cellular behavior, various kinds of wound-healing assays are developed. In these assays, a "wound, " or a "cell-free region, " is created in a cell monolayer mechanically, chemically, optically, or electrically. These assays are useful tools in studying the effects of certain physical or chemical stimuli on the wound-healing process. Most of these methods have disadvantages such as creating wounds of different sizes or shapes, yielding batch-to-batch variation, and damaging the coating of the cell culture surface. In this study, we used ultraviolet (UV) lights to selectively kill cells and create a wound out of a cell monolayer. A comparison between the current assay and the traditional scratch assay was made, indicating that these two methods resulted in similar wound-healing rates. The advantages of this UV-created wound-healing assay include fast and easy procedure, high throughput, and no direct contact to cells.